Low-intensity pulsed ultrasound of different intensities differently affects myocardial ischemia/reperfusion injury by modulating cardiac oxidative stress and inflammatory reaction - Cao, Quan; Liu, Lian; Hu, Yugang; Cao, Sheng; Tan, Tuantuan; Huang, Xin; Deng, Qing; Chen, Jinling; Guo, Ruiqiang; Zhou, Qing (Frontiers in Immunology, 2023)
The prevalence of ischemic heart disease has reached pandemic levels worldwide. Early revascularization is currently the most effective therapy for ischemic heart diseases but paradoxically induces myocardial ischemia/reperfusion (MI/R) injury. Cardiac inflammatory reaction and oxidative stress are primarily involved in the pathology of MI/R injury. Low-intensity pulsed ultrasound (LIPUS) has been demonstrated to reduce cell injury by protecting against inflammatory reaction and oxidative stress in many diseases, including cardiovascular diseases, but rarely on MI/R injury. This study was designed to clarify whether LIPUS alleviates MI/R injury by alleviating inflammatory reaction and oxidative stress. Simultaneously, we have also tried to confirm which intensity of the LIPUS might be more suitable to ameliorate the MI/R injury, as well as tried to clarify the signaling mechanisms. In our study, both in vivo and in vitro, LIPUS of 0.1 W/cm2 (LIPUS0.1) and 0.5 W/cm2 (LIPUS0.5) make no significant difference in the cardiomyocytes under normoxic condition. Under the hypoxic condition, MI/R injury, inflammatory reaction, and oxidative stress were partially ameliorated by LIPUS0.5 but were significantly aggravated by LIPUS of 2.5 W/cm2 (LIPUS2.5) both in vivo and in vitro. The activation of the apoptosis signal-regulating kinase 1 (ASK1)/c-Jun N-terminal kinase (JNK) pathway in cardiomyocytes with MI/R injury was partly rectified LIPUS0.5 both in vivo and in vitro. Our study firstly demonstrated that LIPUS of different intensities differently affects MI/R injury by regulating cardiac inflammatory reaction and oxidative stress. Modulations on the ASK1/JNK pathway are the signaling mechanism by which LIPUS0.5 exerts cardioprotective effects. LIPUS0.5 is promising for clinical translation in protecting against MI/R injury. This will be great welfare for patients suffering from MI/R injury.